2022
DOI: 10.3390/info13020080
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Engaging and Gamified Online Learning Environment—A Real CaseStudy

Abstract: Currently, remote work is common, and this trend has come to several areas and processes, such as education and teaching. Regarding higher education, universities have several challenges to overcome, the most challenging being transforming teaching to be more digital and engaging. Therefore, TechTeach has arisen as a new teaching paradigm that creates a unique learning environment and satisfies students’ and professors’ expectations. After the success of the b-learning approach, professors created new experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In education, student engagement, motivation, creativity, and academic performance are very important, and many researchers use many new technologies and strategies to affect all these positively in which gamification is one of them. Several studies (Topirceanu, 2017;Bernik et al, 2019;Hasan et al, 2019;Portela et al, 2022) highlighted that gamification improves student involvement in learning activities by utilizing a variety of teaching techniques, including tests, escape rooms, and serious games integrated gamification. Furthermore, gamification education platforms help students in terms of motivation to participate in the learning process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In education, student engagement, motivation, creativity, and academic performance are very important, and many researchers use many new technologies and strategies to affect all these positively in which gamification is one of them. Several studies (Topirceanu, 2017;Bernik et al, 2019;Hasan et al, 2019;Portela et al, 2022) highlighted that gamification improves student involvement in learning activities by utilizing a variety of teaching techniques, including tests, escape rooms, and serious games integrated gamification. Furthermore, gamification education platforms help students in terms of motivation to participate in the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tavares (2022) stated that studies utilizing a variety of teaching techniques, including quizzes, escape rooms, and serious games, were generally well-liked by students, who supported their extensive use within their curriculum. Finally, Portela (2022) demonstrated that a classroom can be a stimulating setting where students can learn and have fun whether or not it is physically active, and that gamification can be used to encourage student activities, boost engagement, and evaluate their success.…”
Section: Advantages For Studentsmentioning
confidence: 99%
See 2 more Smart Citations